"Cook &Teach": learning by playing. (1st November 2015) - Bevilacqua, Maurizio; Ciarapica, Filippo Emanuele; Mazzuto, Giovanni; Paciarotti, Claudia
Abstract: Today, different sectors are using Life Cycle Assessment methods to manage risk, create regulation and well-considered policy ad to protect the brand and redesign processes, products and services. Despite their prevalence, Life Cycle Assessment concepts are still not well known in many academic and industrial contexts. In the past, the inability to see the full life cycle of our actions resulted in unexpected consequences in many fields such as increased cancer rates, species and habitat destruction and high levels of waste (both financial and material). This study aims at developing a new educational approach for learning Life Cycle Assessment concepts by applying them to the daily practice of the preparation of meals. The work has been accomplished through several learning games, called "Cook & Teach", in an engineering course at Università Politecnica delle Marche (Ancona, Italy). This study intends to investigate three principal aspects. The first aspect is the change in the student's knowledge of sustainable development. The second is the change in the student's perception of his professional skill development following completion of the project. The last aspect is related to how the student's perception of his motivation and engagement in the project is related to the change in professional skill development. In addition, the game sessions analyzed and discussed in this work show the educational power and training value of the "Cook & Teach" to LCA topics and in particular how the new game facilitates product selection, as confirmed by all of the actors involved. The results obtained highlight that this new educational approach to teach LCA principles stimulated the students' attention and participation. Highlights: This study investigates the use of an LCA game in an engineering course. The game is based on the application of the LCA principles to the preparation of a meal. It is of particular use for educators interested in a new instructional approach. The game structure re-creates a "real" quantitative and operational environment.